American war stories - Boyle, Brenda M., 1957- (War culture., 2021)
"American War Stories asks readers to contemplate what traditionally constitutes a "war story" and how that constitution obscures the normalization of militarism in American culture. The book claims the traditionally narrow scope of "war story," as by a combatant about his wartime experience, compartmentalizes war, casting armed violence as distinct from everyday American life. Broadening "war story" beyond the specific genres of war narratives such as "war films," "war fiction," or "war memoirs," American War Stories exposes how ingrained militarism is in everyday American life, a condition that challenges the very democratic principles the United States is touted as exemplifying"--